Penerapan Konsep Among Ki Hajar Dewantara dalam Mengoptimalkan Keterampilan Berbahasa Siswa - Maf’ula, Dewi; Suherjanto, Indra (Universitas Negeri Malang, 2024)
The use of Indonesian language in the school environment that has not been optimal makes teachers make efforts to develop language skills and encourage students' critical and creative thinking abilities. This study aims to examine and analyze the application of Ki Hajar Dewantara's Among concept in Indonesian language learning as an effort to optimize students' language skills holistically. The method used is a literature study by collecting, analyzing, and synthesizing various relevant literature sources on the concept of Among and Indonesian language learning. The results show that the application of the Among concept which emphasizes teacher exemplary, motivation, guidance, family approach, and democratic principles has high relevance in optimizing students' language skills. Teachers play an important role in applying this concept by being role models, motivators, and mentors for students. Learning strategies and techniques that are aligned with the Among concept such as project-based, collaborative, and contextual learning can be applied to increase students' interest and motivation to learn and develop language skills as a whole. In conclusion, the application of Ki Hajar Dewantara's Among concept in Indonesian language learning is the right solution to realize meaningful, contextual, and aligned learning with national education goals.